Tribological and Antibacterial Properties of Polyetheretherketone Composites with Black Phosphorus Nanosheets - Sun, Xuhui; Yu, Chengcheng; Zhang, Lin; Cao, Jingcao; Kaleli, Emrullah Hakan; Xie, Guoxin (MDPI, 2022)
Over the past few decades, polyetheretherketone (PEEK) artificial bone joint materials faced problems of poor wear resistance and easy infection, which are not suitable for the growing demand of bone joints. The tribological behavior and wear mechanism of polyetheretherketone (PEEK)/polytetrafluoroethylene (PTFE) with black phosphorus (BP) nanosheets have been investigated under dry sliding friction. Compared with pure PEEK, the COF of PEEK/10 wt% PTFE/0.5 wt% BP was reduced by about 73% (from 0.369 to 0.097) and the wear rate decreased by approximately 95% (from 1.0 x 10(-4) mm(3)/(N m) to 5.1 x 10(-6) mm(3)/(N m)) owing to the lubrication of the BP transfer film. Moreover, BP can endow the PEEK composites with excellent biological wettability and antibacterial properties. The antibacterial rate of PEEK/PTFE/BP was assessed to be over 99.9%, which might help to solve the problem of PEEK implant inflammation. After comprehensive evaluation in this research, 0.5 wt% BP nanosheet-filled PEEK/PTFE material displayed the optimum lubrication and antibacterial properties, and thus could be considered as a potential candidate for its application in biomedical materials.
Keywords: black phosphorus; polyetheretherketone; lubrication properties; antibacterial properties; PEEK COMPOSITES; RESTORATIONS; PERFORMANCE; BEHAVIOR; Polymer Science